Efficacy of Jigsaw learning in teaching volleyball skills to grade 12 students - Henreyna Jane C. Redublado; Gino Gasang Sumalinog (CTU Journal of Innovation and Sustainable Development)
Playing volleyball is one of the Physical Education courses in the Philippines. However, playing it is not mastered due to a lack of research-based strategies. This study determined the efficacy of Jigsaw learning in teaching Volleyball in Grade 12 at Biliran Province State University-Main Campus, Naval, Biliran during the academic year 2022–2023 as a basis for a proposed skills enhancement activity. The study used a quantitative descriptive-correlation research design. There were one hundred (100) respondents. The skills performance of the students was good after using jigsaw learning in teaching volleyball as to, serving, passing, setting, spiking/attacking, and blocking. The students’ skills performance before and after using jigsaw learning in teaching volleyball were significantly related. Jigsaw learning was efficient in teaching volleyball. Thus, the Jigsaw model is used to make the students more skillful and competent.